Concussion knowledge among amateur motocross riders - Kristina O Miller; Jody L Langdon; Glenn P Burdette; Thomas A Buckley (Concussion, 2016)
Aim: There has been considerable increase in concussion awareness and risks; however, extreme sports such as motocross have received scant attention. The purpose of this study was to assess concuss...